(untitled) (Studia Prawnicze / The Legal Studies, 1985)
The article presents Weber’s concept of explanation of human actions on the basis of the assumptions of rationality and meaning and functions of rational action in J. Wróblewski’s works. Certain common methodological ideas of both scholars have been pointed to, as well as differences in understanding the cognitive role of typical-ideal constructions of Weber’s rational action and Wróblewski’s theoretical model of such an action.